A Novel Quantum-Enhanced Algorithm for Dynamic Soil Microbiome Optimization to Boost Agriculture - Mukherjee Anshit (EPJ Web of Conferences)
Present methods for sustainable soil microbiome management through effective solutions must address microbial complexity. Quantum computing systems provide revolutionary power that enables solutions to the difficulties observed in these applications. The research establishes an algorithm that combines quantum annealing with hybrid neural networks along with quantum walks optimization for nutritional pathway and microbial relationship simulation. The research implements three quantum computing developments which are Quantum-Classical Symbiosis Architecture and Dynamic Quantum Walk Optimization for nutrient pathways and Multi-scale Quantum Tomography for non-destructive microbiome imaging. The synthesis engine of biofertilizers relies on quantum optimization to interpret rhizosphere chemical gradients which leads to consortia formulation. Research in agricultural fields demonstrated that the nutrient efficiency improved by 32% while the crop yield increased by 19%. Quantum optimization processed data 78% faster than baseline systems because of which it could instantly respond to fluctuating soil conditions. The quantum framework design at multiple levels allows precise management of agro-bio systems which helps build agricultural systems that resist climate change. Research into predictive microbiome management strategies will extend to different geographical zones across agroclimatic regions.